BARRIERS TO IMPLEMENTING ETHICS AND COURTESY IN HEALTHCARE COMMUNICATION AT SIDOARJO COMMUNITY HEALTH CENTERS - Susilo, Zora Calista; Fitranisa, Intan; Ahmad Abduh Haris Hikam; Angelita Theresia Rumondang Limbong; Arief Rifqi Slamet Zuhdi; Lesmana, Aurelya; Ghaida Tsurayya Haq; ⁠Ierica Regitha Syahira Maharanti; Michael Gery Wicaksono; Rahma Mareta Kartika Putri; Satriyani Dewi Astuti (Universitas Airlangga, 2025)
Healthcare providers at community health centers frequently interact with patients and their families from diverse backgrounds. This diversity presents distinct challenges, particularly when communicating about the healthcare services offered by the centers while maintaining ethical standards and courtesy toward both patients and their families. This study, therefore, aims to explore the barriers to implementing ethics and courtesy in healthcare communication following specialized communication training, particularly within Sidoarjo’s community health centers. The communication training was a full-day event organized by the Department of Communication at Universitas Airlangga and included ten representatives from various community health centers across Sidoarjo as participants. Following the training, participants received five days of supervised practice in health communication at their respective centers, concluding with questionnaire responses and in-depth interviews to assess obstacles to implementing ethics and courtesy in healthcare communication. The study findings indicate that factors such as negative perceptions, limited openness, and inadequate emotional support significantly hinder the implementation of ethical and courteous communication within healthcare services in Sidoarjo.